CircRNA hsa_circ_0018289 exerts an oncogenic role in cervical cancer progression through miR‐1294/ICMT axis. Issue 5 (21st March 2022) - Li, Yujuan; Gao, Xiangrong; Yang, Chaochao; Yan, Hua; Li, Cui
Abstract: Background: circRNA hsa_circ_0018289‐mediated growth and metastasis of CC cells were investigated, as well as the mechanistic pathway. Methods: Quantitative real‐time reverse transcription‐polymerase chain reaction (qRT‐PCR) was carried out to examine the expression of hsa_circ_0018289, microRNA (miR)‐1294, and isoprenylcysteine carboxyl methyltransferase (ICMT). CC cell proliferation, migration, and invasion were evaluated by 5‐ethynyl‐2'‐deoxyuridine (EdU) incorporation, colony formation, transwell assays, Western blot analysis of ICMT, and glycolysis‐associated proteins. Dual‐luciferase reporter or RNA pull‐down analysis of the target interaction between miR‐1294 and hsa_hsa_circ_0018289 or ICMT. Xenograft model assay was implemented to assess the role of hsa_circ_0018289 in vivo. Immunofluorescence (IHC) was employed to detect the level of Ki‐67. Results: Hsa_circ_0018289 was elevated in CC tissues and cells, its deficiency could repress growth, metastasis, and glycolysis of CC cells in vitro, as well as hamper tumor growth in vivo. Hsa_circ_0018289 sponged miR‐1294 while miR‐1294 bound with ICMT, and the inhibition of miR‐1294 or addition of ICMT could partially relieve the effect caused by hsa_circ_0018289 depletion. Conclusion: Hsa_circ_0018289 contributes to malignant development by regulating the miR‐1294/ICMT axis, affording novel insight into CC therapy. Abstract : Schematic diagram of circ_0018289 regulating CC cell malignancy behavior.